Appraising the Phytochemical and Therapeutic Perspectives of Bryonia laciniosa: A Literature Metasynthesis - Katiyar, Deepti; Saxena, Rashmi; Kumar, Abhishek; Prakash, Surya; Bhardwaj, Abhay; Bansal, Priya (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Nature has bestowed mother Earth with an array of herbals utilized as therapeutics for various human ailments since the origin of life. Bryonia laciniosa (family: Cucurbitaceae) is one such herb, which finds its mention in various traditional systems of medicine and has attracted current researchers due to its significant therapeutic value. Objective: The current article aims to present a literature metasynthesis on Bryonia laciniosa. Methods: The authors performed scholarly searches for peer-reviewed findings on Bryonia laciniosa and incorporated all the data related to the phytochemical and therapeutic profile of the drug. Results: This compilation comprises of Phytochemical and Pharmacological profile of Bryonia laciniosa elaborating its traditional significance and recent researches related to its biological activities. The plant exhibits its potential as an antimicrobial, anti-inflammatory, analgesic, antipyretic, anticonvulsant, anti-asthmatic, anticancer, antioxidant, antidiabetic, and aphrodisiac agent. It also displays its benefits in wound healing and ulcerative colitis. Conclusion: The presence of flavonoids, saponins, terpenoids, anthocyanins, coumarins, alkaloids, polyphenols, tannins and emodins in this plant is responsible for its various pharmacological activities. The retrospective study provides direction for existing research as well as future studies to support the domain of pharmaceutical and medical sciences.
Keywords: cucurbitaceae